Motion of two discs joined by strings in S-type connection - Artuković, Ranko (Array, 2008)
Summary: Motion of a pair of discs under the action of the centrifugal force and string tension is studied. The discs can slide along a guide-bar and rotate around their axes. Initially, each disc is held symmetrically with respect to the main axis of rotation by a string which is wound around it and tied to a cross-bar. While the assembly rotates around the main axis, the discs are released by cutting the two strings in a way that the configuration resembles the letter S. The discs start moving from the main axis and change rotation around their axes. Their motion is analysed using equations of motion and the law of conservation of angular momentum. The results are verified using the law of conservation of energy. It is found that after a long time, rotation of the guide-bar stops, and the two discs move symmetrically from the main axis with the same speed and rotate with the same angular velocity. An interesting result is that the angle of rotation of the guide-bar does not depend on the initial angular velocity of the assembly